Propuesta de mejora para incrementar la productividad en la fabricación de placas expandidas de baterías plomo-ácido a través de balanceo de líneas (2021)
Lead-acid batteries are generally used in conventional and electric vehicles, its manufacturing process is characterized by having a long series of routine activities. The purpose of this work is to design a proposal for improvement using line balancing to increase productivity in the production process of expanded plates in this type of batterie. It seeks to equate workloads on workstations, minimize idle time and optimize production time. For this, three great stages were carried out. The first one consisted of characterize the manufacturing process using work study tools; then a literature review about assembly line balancing methods was conducted, and alternative solutions were identified. Finally, a solution method for a SALBP-1 type problem was defined and evaluated. The obtained results showed a reduction in the number of stations that implies improvements in the process, mainly in the productivity of the line and its operators.